Scirpetum radicantis Hejný in Hejný et Husák 1978 em. Zahlh. 1979, a plant association new to Poland - Krzysztof Spałek; Arkadiusz Nowak (Acta Societatis Botanicorum Poloniae, 2011)
The paper presents a rush community new to Poland - Scirpetum radicantis Hejny in Hejny et Husak 1978 em. Zahlh. 1979, belonging to the Phragmition alliance. It was discovered in fishponds near Olesno in Silesia (SW Poland). The floristic composition and the ecological requirements of this association are presented in the paper. Scirpetum radicantis is considered to be a very rare and endangered plant community in Europe.